Effect of forsterite addition on the densification and properties of hydroxyapatite bioceramic - Ramesh S.; Virik N.S.; Bang L.T.; Niakan A.; Tan C.Y.; Purbolaksono J.; Yap B.K.; Teng W.D. (Hanyang University, 2023)
The effect of forsterite addition on the phase stability, microstructure and mechanical properties of hydroxyapatite was studied. In the present work, three different forsterite-doped hydroxyapatite (HA-F) compositions were prepared i.e. 5, 10 and 20 wt% forsterite. The HA-F ceramics were prepared by ball milling followed by sintering in air at temperatures ranging from 1100 C to 1350 C. The sintered bodies were evaluated in terms of the phase stability, grain size, relative density, Vickers hardness, fracture toughness and Youngs modulus. It was found that the presences of forsterite promoted the decomposition of hydroxyapatite, was effective in suppressing grain coarsening and improved the fracture toughness of the sintered body. The results revealed that the mechanical properties of the composite was governed by both the grain size and bulk density. 2016, Hanyang University. All rights reserved.